1981
DOI: 10.1111/j.1471-4159.1981.tb02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Hydroxylase Activation and Inactivation by Protein Phosphorylation Conditions

Abstract: Tyrosine hydroxylase, the rate-limiting enzyme in catecholamine biosynthesis, catalyzes the conversion of tyrosine to DOPA, Cyclic AMP-dependent protein phosphorylation conditions alter tyrosine hydroxylase activity in rat striatal homogenates. In agreement with other laboratories, we find that short-term pre-incubation (3 min) of extracts under phosphorylating conditions (Mg . ATP, cAMP) increases enzyme activity two- to tenfold over control as measured during a subsequent 15-min assay. We now report that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Tyrosine hydroxylase (TH), the rate‐limiting enzyme for the synthesis of catecholamines, undergoes PKA‐dependent phosphorylation, resulting in enzyme activation (Kumer and Vrana, 1996). Multiple‐site phosphorylation and activation of striatal TH occur in vivo and in vitro (Joh et al, 1978 ; Vrana et al, 1981 ; Haycock, 1987 ; Salah et al, 1989 ; Haycock and Haycock, 1991). We have previously shown that the activities of AAAD and TH of striatum are modulated in parallel by cyclic AMP (presumably PKA)‐dependent pathways in vivo (Young et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosine hydroxylase (TH), the rate‐limiting enzyme for the synthesis of catecholamines, undergoes PKA‐dependent phosphorylation, resulting in enzyme activation (Kumer and Vrana, 1996). Multiple‐site phosphorylation and activation of striatal TH occur in vivo and in vitro (Joh et al, 1978 ; Vrana et al, 1981 ; Haycock, 1987 ; Salah et al, 1989 ; Haycock and Haycock, 1991). We have previously shown that the activities of AAAD and TH of striatum are modulated in parallel by cyclic AMP (presumably PKA)‐dependent pathways in vivo (Young et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in activity with increasing time of phosphorylation has also been reported in studies with cAMP-dependent phosphorylation of tyrosine hydroxylase (e.g., see ref. 31) and has been attributed to an increased susceptibility to denaturation of the phospho form of the enzyme relative to the dephospho form (32). There was little or no change in tyrosine hydroxylase activity as a function of time of preincubation in the absence of protein kinase C (Fig.…”
mentioning
confidence: 99%
“…An altered synthetic rate equips the cell to deal with longterm neural demands. More rapid alteration in enzyme activity can be effected by activation or inactivation of existing TH molecules (38). Because of the rapidity of the fall and rise in TH activity noted within the first 9 hours after HSV-1 infection, we anticipated that, inactivation and activation of TH likely accounted for our experimental findings.…”
Section: Discussionmentioning
confidence: 95%
“…either from activation of existing enzyme molecules or synthesis of new enzyme (25,38,40,41). In order to distinguish which of these processes predominated in determining the alterations in TIt activity accompanying HSV-1 infection, we carried out an immunotitration assay using antibody against TH (3, i4, 4t).…”
Section: Assessment Of Altered Th Activity By Immunotitrationmentioning
confidence: 99%